Exploring correlations of energy companies on Bursa Malaysia during the Covid-19 pandemic using network analysis - Hafizah Bahaludin,; Alyssa April Dellow,; Mimi Hafizah Abdullah,; Munira Ismail,; Fatimah Abdul Razak, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The COVID-19 pandemic has profoundly disrupted the global economy, and the energy sector has been particularly hard hit. With a sharp decline in the global economic outlook, the energy industry faced significant challenges, including a substantial drop in oil prices that reverberated throughout energy markets worldwide. In light of this unprecedented situation, our study aims to delve into the impact of COVID-19 on Shariah-compliant energy stocks listed on Bursa Malaysia between 2019 and 2020. To accomplish this, we employed the triangulated maximally filtered graph (TMFG) approach for analysing intricate datasets. By constructing networks using the TMFG technique and employing the degree centrality measure on 26 energy stocks in the pre-COVID period (2019) and during the COVID period (2020), we examined the structural changes and correlations within the networks. Notably, our findings reveal that the correlation among energy stocks became even stronger during the COVID period, highlighting the sector’s heightened interdependence. Additionally, our analysis identifies Hibiscus Petroleum Bhd (HIBI) as the most influential stock throughout both timeframes, underscoring its significance amidst the pandemic-induced market fluctuations. These research outcomes carry significant practical implications, such as offering valuable insights to market participants in navigating the energy market’s evolving landscape, which then enables informed decision-making for portfolio management and effective policy implementation.